Power ultrasonic assisted mixing and proofing during bread making process - Che Pa, Nasrul Fikry (2014)
Power ultrasonic assisted mixing and proofing processes were investigated in parallel by varying the ultrasonic duration and power level factors in both processes. The effects of power ultrasonic during both mixing and proofing processes on the physical and textural properties of bread such as volume, mass, density and firmness,and also on the crumb structure of bread such as void fraction, mean cell area,average cell diameter, crumb fineness, mean cells per area and cell uniformity were studied. Both studies required the design and fabrication of an ultrasonic bath system at a frequency of 25 kHz and with a temperature controller and timer. Power levels of 1.00, 1.50, 2.05 and 2.50 kW and durations of 10, 20, 30, and 40 minutes (for mixing); 15, 30, 45, 60 minutes (for proofing) were used. A simplified algorithm using Vision Assistant 2009 (National Instruments) imaging software was developed to assist in crumb structure analysis of bread. A preliminary study using the dough dynamic density method in the mixing study gave convincing results of the effects of ultrasonic exposure as a significantreduction in dough density was demonstrated. Power ultrasonic assisted mixing significantly altered the physical and textural properties with the bread volume increasing by 19.0 %, while bread mass, density and firmness were reduced by 2.1 %, 17.0 %, 34.1 %, respectively using the maximum ultrasonic power of 2.50 kW with the longest ultrasonic duration exposure of 40 minutes. Examination of the crumb structural characteristics showed a significant increase of void fraction, mean cell area and average cell diameter of 47.3 %, 41.7 % and 12.4 %, respectively with the maximum ultrasonic power level and exposure albeit the value can go up to 51.6 % and 15.6 % each for mean cell area and average cell diameter with reduced power level of 1.50 kW and 30 minutes of exposure. The results suggested that power ultrasonic increased bread aeration when applied during the mixing process with both ultrasonic duration and power level giving significant impact at minimally P < 0.05. Similarly, ultrasonic assisted proofing enhanced bread aeration with the majority of the maximum values in the tests at 1.50 kW. Bread volume, void fraction, mean cell area and average cell diameter showed an increase of 17.1 %,20.8 %, 20.9 %, 6.7 %, while reductions were shown for bread mass, density and firmness at 2.5 %, 16.7 %, 24.1 % respectively with the overall P < 0.001. Based on the findings shown, it is suggested that bread aeration is significantly improved under prolonged duration of ultrasonic proofing, particularly above 45 minutes of exposure with ultrasonic duration governing the changes. However, detrimental effects prevailed when power levels exceeded 1.50 kW. Yeast injuries were suspected as the major reason for the detrimental effects shown based on a literature study. Overall,power ultrasonic was proven to impose significant changes in both the physical and textural properties of the bread and also the crumb structures when employed during the mixing and proofing processes.